Strategi Komunikasi Pemasaran Dalam Mempromosikan Batik Putri Sanggabuana Karawang Sebagai Identitas Budaya Lokal - Pitrianingsih, Devi; Isyanto, Puji; Sumarni, Neni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the marketing communication strategy of Batik Putri Sanggabuana Karawang in promoting batik as a local cultural identity, as well as identify the obstacles that affect the effectiveness of the strategy. Using a qualitative approach with a case study method, data were obtained through in-depth interviews, observation, and document analysis. The results show that social media, collaboration with influencers, and cultural campaigns have increased public awareness of Batik Karawang, although there are still constraints such as budget limitations and low local appreciation. A more creative marketing strategy is needed to strengthen Putri Sanggabuana Batik's position as local cultural pride. This study implies the importance of collaboration between the government, community, and entrepreneurs in preserving and promoting batik as a cultural heritage and improving its competitiveness in the domestic and global markets.